Development of LKPD Based on Ethnomathematics of Kediri Local Culture on Two-Dimentional Figure - Amalia, Fitri Annisa’ Rizka; Rofiah, Tutik Dinur; Annisa, Choirul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
Many students who consider mathematics to be one of the subjects that are difficult to master. This is due to the lack of learning resource facilities and learning activities that focus on teachers. Students do not understand the local culture in their region and the potential of their region of origin also. So, in this research will examine how to develop LKPD based on ethnomathematics of Kediri local on mathematic studies. The objectives of this study are to describe the development process, media suitability, and the effectiveness of LKPD based on ethnomathematics of Kediri local culture on the understanding of the concept of two-dimentional figure in grade IV. The development uses the type of R&D research with the ADDIE development model. This research obtained results, they get a very decent level, namely 96.67% by material expert 1 and 83.33% by material expert. From the teaching material expert, the level is very feasible, namely 98.75% by the teaching material expert 1 and 87.5% by the teaching material expert. The effectiveness of the product is seen from the t-test using paired sample t-test 0,004 in small group and 0,000 in large group. N-Gain test In the small group trial, the N-Gain Score of 0.56 was included in the medium category. Meanwhile, in the large group trial, the N-Gain Score of 0.64 is included in the medium category. The conclusion is that this development research is able to increase understanding of the concept of two-dimentional figure.